DEVELOPMENT OF DIGITAL COMPETENCE OF FUTURE PHILOLOGISTS: CASE OF TURKISH AND UKRAINIAN UNIVERSITIES - Liliya Baranovska; Iryna Simkova; Erman Akilli; Tetyana Tarnavska; Nataliia Glushanytsia (Novìtnâ Osvìta, 2023)
The paper calls into question the development of the digital competence of future philologists, taking into account the Turkish and Ukrainian experiences. The study of digital competence development is attracting increasing interest due to a growing need for experts capable of processing the enormous streams of continuously transmitted information and experts willing to improve their digital skills for professional growth. The purpose of the study is to broaden the current knowledge about the ways of developing digital competence. In this respect, the paper investigates two systems of future philologists' training in Ukraine and Turkey in the Digital Tools for Translation course. The authors analyze the experience of the Turkish and Ukrainian higher education institutions regarding the use of appropriate ICT tools using theoretical and empirical methods. Fifty-two future philologists from Turkey and Ukraine took part in the research. The study presents the results from observing the training and interviews with Ukrainian and Turkish students. The Shapiro-Wilcoxon method (non-parametric criterion) was used to verify the results. An analysis has highlighted the positive experience of Turkish universities, which can be implemented in future philologists training in Ukrainian universities. The findings of this study support the idea that the insufficient level of digital competence development lengthens and complicates the period of adaptation of graduates to modern working conditions. The authors found that the integration of Ukrainian higher education into the European higher education area occurs in times of globalization and the digitalization of society, which radically changes the nature of many activities. This research has clearly shown that digital competence development is more effective with the implementation of a holistic approach when students enhance digital competence while acquiring all other competencies. Our research suggests that the digitalization of education reduces the gap between graduates' digital competence level and modern society's expectations.